Pemberdayaan Ekonomi KWT Bawang Ceria Melalui Penerapan Teknologi Spinner Otomatis dalam Produksi Keripik MOCAF - Afifah, Dini Nur; Hamad, Alwani; Haq, M Tsabit Sofatul; Mauliana, Dinda; Hartanti, Dwi; Wiranata, Ardi (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2025)
This community service program aims to address the problem of excessive oil content in MOCAF dumpling chips produced by the Bawang Ceria Farmer’s Women Group in Banjarnegara. The previous manual draining process was found to be ineffective, causing the product to turn rancid quickly and have a short shelf life. As a solution, the implementation team introduced an oil spinner machine based on a centrifugal system equipped with automatic speed control. The program was carried out through socialization, hands-on training, and a joint technology trial with the member group. The results indicate that the spinner effectively reduced oil content by approximately 10%, producing chips with a crispier texture and a more appealing appearance. The integrated dimmer and automatic timer features ensured stable processing and consistent product quality. Although a slight decrease in savory flavor was noted due to reduced oil content, the overall product remained well accepted by consumers. Furthermore, the training activities significantly enhanced the members’ understanding and technical skills, as reflected in an increase in knowledge level from 24.61% to 80.48%.